The potential use of spent mushroom waste from Pleurotus ostreatus cultivation as ruminant feed - Shaharul Badri, Amirul Hakim (2015)
Spent mushroom compost (SMC), otherwise known as spent mushroom substrate (SMS), or spent mushroom compost (SMW), is the leftover after different flushes of growing and cropping mushroom. Oyster mushroom (Pleurotus ostreatus) is a white, gray-brown or ivory coloured mushroom which resembles oyster shell. This study was conducted in Universiti Putra Malaysia to evaluate the nutrient composition and digestibility of ensiled guinea grass treated with spent mushroom waste in goats. The main objective of this study is to determine the dry matter intake of the feed, nutrient digestibility, and daily weight gain of the goats. A total of 4 adult crossbred Kacang goats were allocated in each pen and given 4 dietary treatments which were 0% spent mushroom waste as a control (T1), 5% spent mushroom waste (T2), 10% spent mushroom waste (T3), and 15% spent mushroom waste (T4). They were given 10 days adjustment period followed by 7 days collection period. Feed intake and feces were weighed during 7 days of collection. Samples of feed, and feces were analyzed for dry matter, ash, crude protein, NDF, ADF, and ADL. All data on nutrient composition, digestibility, and daily weight gain were subjected to one way analysis of variance with SAS version 9.3. No significant difference (P > 0.05) in dry matter intake of the goats with every dietary treatment given. There was no significant difference (P > 0.05) in nutrient digestibility of the feces and feed. But, there is a significant difference (P < 0.05) in ADL digestibility. The ADL digestibility increase from 5.966% in T1 to 9.905 in T3 and decrease to 8.753% in T4. There is no significant difference (P > 0.05) in weekly gain of goats in each treatment. These findings could be due to animal’s preference for forages over ensiled guinea grass treated with spent mushroom waste, and feed may had strong ammonia odor. It can be concluded that there is no significant different in giving spent mushroom waste in feed intake, digestibility, and weight gain of the animals. Further study is required to increase the digestibility and palatability of the sawdust-based spent mushroom waste.